Gambaran tingkat pengetahuan tentang Periksa Payudara Sendiri (SADARI) pada mahasiswa Fakultas Kedokteran Universitas Udayana, Bali, Indonesia angkatan 2013-2015 - Annisa Alviariza; Putu Anda Tusta Adiputra (DiscoverSys Inc., 2020)
Background: BSE (Breast Self-Examination) is a systematic approach to inspection and palpation examination of the chest and armpit independently. BSE can be used as a means of early detection of breast cancer using a simple, inexpensive and safe. This study aims to determine the level of knowledge about BSE among students of Medical Education Faculty of Medicine Udayana University class of 2013, 2014 and 2015.Methods: A descriptive cross-sectional study was conducted among 285 respondents at Faculty of Medicine, Medical Education Program class of 2013, 2014, and 2015. The instrument used in this study was a valid and reliable questionnaire to identify the respondents' knowledge about breast cancer and BSE. Questionnaire data that has been collected is processed in the form of descriptive data analysis by calculating proportion and percentages. Data were analyzed using SPSS version 17 for Windows.Results: The highest average score about SADARI were obtained in Class 2013 (75%), followed by Class 2014 (72%), and Class 2015 (67%) students. A high level of knowledge criteria about SADARI also suggest similar results where Class 2013 was having the highest percentage (63%), followed by Class 2014 (25%), and Class 2015 (8%). However, based on the overall results, the students had a moderate score of 66%. Besides, according to the questions on the questionnaire, the students had an excellent average score about signs and symptoms (83%), cause (79%), and stage of breast cancer (79%).Conclusion: Class 2013 had a good level of knowledge regarding SADARI compared with Class 2014 and 2015. However, overall students still at a moderate average score of SADARI. Latar Belakang: SADARI (Periksa Payudara Sendiri) adalah metode sistematik untuk pemeriksaan inspeksi dan palpasi dada dan ketiak secara mandiri. SADARI dapat digunakan sebagai cara deteksi dini kanker payudara dengan menggunakan cara yang sederhana, murah dan aman. Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan mengenai SADARI Mahasiswa Pendidikan Dokter Fakultas Kedokteran Universitas Udayana angkatan 2013, 2014 dan 2015.Metode: Sebuah studi potong lintang deskriptif dilakukan terhadap 285 responden di Fakultas Kedokteran, Program Pendidikan Kedokteran kelas 2013, 2014, dan 2015. Instrumen yang digunakan dalam penelitian ini adalah kuesioner yang sahih dan reliabel untuk mengidentifikasi pengetahuan responden tentang kanker payudara dan BSE. Data kuesioner yang telah dikumpulkan diolah dalam bentuk analisis data deskriptif dengan menghitung proporsi dan persentase. Data dianalisis menggunakan SPSS versi 17 untuk Windows.Hasil: Nilai rata-rata tertinggi tentang SADARI diperoleh pada siswa di Kelas 2013 (75%), diikuti oleh Kelas 2014 (72%), dan Kelas 2015 (67%). Kriteria tingkat pengetahuan tinggi tentang SADARI juga memberikan hasil yang serupa di mana Kelas 2013 memiliki persentase tertinggi (63%), diikuti oleh Kelas 2014 (25%), dan Kelas 2015 (8%). Namun, berdasarkan hasil keseluruhan, para siswa memiliki skor sedang 66%. Selain itu, menurut pertanyaan pada kuesioner, para siswa memiliki skor rata-rata yang sangat baik tentang tanda dan gejala (83%), penyebab (79%), dan stadium kanker payudara (79%).Kesimpulan: Kelas 2013 memiliki tingkat pengetahuan yang baik tentang SADARI dibandingkan dengan Kelas 2014 dan 2015. Namun, keseluruhan siswa masih berada pada skor rata-rata SADARI yang moderat.